Comparison of maximum muscle strength and isokinetic knee and core muscle functions according to pedaling power difference of racing cyclist candidates - Park, J. H.; Kim, J. E.; Yoo, J. I.; Kim, Y. P.; Kim, E. H.; Seo, T. B. (Journal of Exercise Rehabilitation, 2019)
The purpose of this study was to investigate differences of maximum muscle strength and isokinetic knee and core muscle functions according to pedaling power of racing cyclist candidate. Subjects for this study were 200 racing cyclist candidates and divided into four groups: top 10% peak power group (TPP, n=20), low 10% peak power group (LPP, n=20), top 10% average power group (TAP, n=20), and low 10% average power group (LAP, n=20). The maximum muscle strength was consisted of grip strength, bench press and squat measured by Ariel device, and isokinetic knee and core muscle functions were analyzed by Humac Norm device. Significant differences between groups were determined with one-way repeated analysis of variance. As the result of this study, TPP and TAP groups showed significantly decreased body-fat mass and increased free fat mass when compared to LPP and LAP groups. The maximum strength of grip and squat was significantly higher in TPP and TAP than in other groups. Isokinetic knee extension and flexion strength was higher in TPP and TAP groups as well as isokinetic trunk extension and flexion functions were highest in TPP group. Thus, our findings suggest new evidence that muscle mass, maximal muscle strength, and isokinetic muscle functions might be important predictors of racing cyclist performance.